2013
DOI: 10.1177/1049909113481100
|View full text |Cite
|
Sign up to set email alerts
|

Hardships of End-of-Life Care With Court-Appointed Guardians

Abstract: In the United States, the court-appointed guardians do not have the ability to make decisions regarding end-of-life (EOL) care for their clients. Additionally, the process of initiating EOL care measures can be slow and cumbersome, despite an existing process of getting approval for such care. This process has the potential to prolong suffering and delay imperative decisions. This article reviews the hardships that patients, court-appointed guardians, and health care staff endure while moving through the oppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Reports have long suggested that they choose instead the “safer” path of aggressive care by default or defer to a cumbersome judicial process. 12–17 Physicians are in a unique position to assist guardians with these difficult decisions and to collaborate with them to protect the rights and dignity of the vulnerable persons they represent. Doing so, however, requires knowledge of the laws governing guardians, particularly those concerning what decisions a guardian is allowed to make and when judicial review is required.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have long suggested that they choose instead the “safer” path of aggressive care by default or defer to a cumbersome judicial process. 12–17 Physicians are in a unique position to assist guardians with these difficult decisions and to collaborate with them to protect the rights and dignity of the vulnerable persons they represent. Doing so, however, requires knowledge of the laws governing guardians, particularly those concerning what decisions a guardian is allowed to make and when judicial review is required.…”
Section: Introductionmentioning
confidence: 99%
“…When pivotal choices arise near the end of life, case studies and clinical experience have led experts to suggest that professional guardians respond in two potentially problematic ways. One is by selecting high‐intensity treatment regardless of the likely benefit because the guardian perceives this to be the “safer” course . The other is by avoiding complex decisions and leaving them to the court, whether or not the law requires the guardian to do so .…”
mentioning
confidence: 99%
“…One is by selecting high-intensity treatment regardless of the likely benefit because the guardian perceives this to be the "safer" course. [2][3][4] The other is by avoiding complex decisions and leaving them to the court, whether or not the law requires the guardian to do so. 5 The result is that highintensity treatment is delivered by default while health professionals wait for a judge to make a decision.…”
mentioning
confidence: 99%
“…Depending on state laws, guardians may be limited in their capacity to withdraw lifeextending treatment such as artificial feedings. 9,11 In such cases, involvement of social work and bioethics may be necessary.…”
Section: Illness Backgroundmentioning
confidence: 99%